Opening the Door: How the Regional Autonomy Has Made the Implementation of Perda Sharia Possible? - Erwin Nur Rif'ah (International Journal of Nusantara Islam, 2014)
Sharia-influenced regional regulations (perda sharia) are regulations or laws that are created by district governments and use Islamic moral teachings as a reference point. This article based on a qualitative research in two districts: Cianjur, West Java and Bulukumba South Sulawesi.  In general, perda sharia seeks to manage three aspects of public life: firstly, to eradicate moral and social problems such as prostitution, drinking alcohol and gambling; secondly, to enforce ritual observances among Muslims such as reading the Qur’an, attendance at Friday prayers and fasting during Ramadan, and thirdly, to govern the way people dress in the public sphere, especially in relation to head-veiling for the women.